2018
DOI: 10.1523/eneuro.0104-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

ΔFosB Decreases Excitability of Dorsal Hippocampal CA1 Neurons

Abstract: Both the function of hippocampal neurons and hippocampus-dependent behaviors are dependent on changes in gene expression, but the specific mechanisms that regulate gene expression in hippocampus are not yet fully understood. The stable, activity-dependent transcription factor ΔFosB plays a role in various forms of hippocampal-dependent learning and in the structural plasticity of synapses onto CA1 neurons. The authors examined the consequences of viral-mediated overexpression or inhibition of ΔFosB on the func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 55 publications
2
21
0
Order By: Relevance
“…Moreover, ΔFosB decreased amplitude and increased half-width of evoked action potentials and decreased the frequency of spontaneous synaptic currents ( Fig. S10c-f), similar to what we have previously observed in dHPC CA1 neurons 18 . This suite of observations suggests that ΔFosB expression reduces the excitability of vHPC neurons, likely via changes in intrinsic membrane properties.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Moreover, ΔFosB decreased amplitude and increased half-width of evoked action potentials and decreased the frequency of spontaneous synaptic currents ( Fig. S10c-f), similar to what we have previously observed in dHPC CA1 neurons 18 . This suite of observations suggests that ΔFosB expression reduces the excitability of vHPC neurons, likely via changes in intrinsic membrane properties.…”
Section: Resultssupporting
confidence: 89%
“…Because the excitability of afferent projections from vHPC CA1 extending to NAc mediate CSDS susceptibility 4 and ΔFosB regulates excitability of dHPC CA1 neurons 18 , we set out to investigate the role of vHPC projection neuron ΔFosB in CSDS susceptibility to social avoidance. To label vHPC-NAc neurons, we utilized a mouse line expressing Cre-dependent GFP-L10a ribosomal subunit fusion protein (Rosa26 eGFP-L10a ), and injected into NAc a persistent, retrograde viral vector expressing Cre (HSV-hEf1ɑ-Cre).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that ΔFosB expression in the hippocampus also decreases neuronal activity [41]. We therefore conclude that the activity of ΔFosB-expressing neurons in both the mPFC and VTA would also decrease, and this decrease is greater in BEP than in BER rats.…”
Section: Discussionsupporting
confidence: 47%
“…In this region, GABAergic neurons inhibit the activity of dopaminergic neurons. ΔFosB reduces the activity of ΔFosB-expressing neurons [36, 41]. As the proportion of GABAergic ΔFosB-expressing neurons was lower in BEP rats, it suggests that the GABAergic neuronal activity is less reduced in BEP rats compared to BER rats.…”
Section: Discussionmentioning
confidence: 99%